2014
DOI: 10.2174/13894501113149990210
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone/Naloxone in the Management of Patients with Pain and Opioid–Induced Bowel Dysfunction

Abstract: OXN is an important drug for chronic pain management, prevention and treatment of OIBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The initial dose should be titrated to achieve effective analgesia and acceptable adverse effects. Currently, OXN is approved in daily doses of up to 80/40 mg (16); however, controlled studies in patients with nonmalignant (17) and cancer-related pain (18) demonstrated that the daily dose of 120/60 mg might be safe and effective. On the other hand, Mercadante et al (19) reported a patient with severe cancer pain, which required high daily doses of OXN (240/120 mg) that were ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…The initial dose should be titrated to achieve effective analgesia and acceptable adverse effects. Currently, OXN is approved in daily doses of up to 80/40 mg (16); however, controlled studies in patients with nonmalignant (17) and cancer-related pain (18) demonstrated that the daily dose of 120/60 mg might be safe and effective. On the other hand, Mercadante et al (19) reported a patient with severe cancer pain, which required high daily doses of OXN (240/120 mg) that were ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…The available OXY/NLX doses are in a ratio of 2:1 with 5/2.5 mg, 10/5 mg, 20/10 mg, and 40/20 mg [ 77 ]. The optimal 2:1 ratio was reported in a four-arm clinical trial ( N = 202) where subjects were treated with OXY dosed 40 and 80 mg daily and NLX with varying doses of 0, 10, 20, and 40 mg [ 78 ].…”
Section: Oxycodone (Oxy)/naloxone (Nlx)mentioning
confidence: 99%
“…[ 82 ]. Clinicians should constantly monitor patients using this product for both chronic pain management and constipation pharmacotherapy [ 77 ].…”
Section: Oxycodone (Oxy)/naloxone (Nlx)mentioning
confidence: 99%
“…In four published studies, two showed equivocal results. However, two studies documented significant improvement in postoperative bowel functions, one also improved the passing of urine, an often neglected adverse effect of postoperative pain treatment with opioids [11][12][13]. The study by Comelon and co-workers [13] on bowel functions after laparoscopic hysterectomies did not find effects on postoperative bowel function when comparing OxyContin ® 10 mg without naloxone with OxyContin ® 10 mg with 5 mg naloxone added (= Targin ® , Targiniq ® , Targinact ® ) twice daily.…”
Section: Oral Prolonged Release Naloxonementioning
confidence: 99%